2022
DOI: 10.1038/s41467-021-27702-w
|View full text |Cite
|
Sign up to set email alerts
|

Reactive astrocytes acquire neuroprotective as well as deleterious signatures in response to Tau and Aß pathology

Abstract: Alzheimer’s disease (AD) alters astrocytes, but the effect of Aß and Tau pathology is poorly understood. TRAP-seq translatome analysis of astrocytes in APP/PS1 ß-amyloidopathy and MAPTP301S tauopathy mice revealed that only Aß influenced expression of AD risk genes, but both pathologies precociously induced age-dependent changes, and had distinct but overlapping signatures found in human post-mortem AD astrocytes. Both Aß and Tau pathology induced an astrocyte signature involving repression of bioenergetic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 90 publications
5
83
1
Order By: Relevance
“…Our study and the one by Jiwaji and colleagues are highly complementary since present different methodologies. More specifically, studies used different brain regions (hippocampus vs whole cortex and spinal cord) and cell-sorting protocols that isolated distinct astrocyte populations (GFAP-positive astrocytes vs pan astrocytes) (5). Despite the exciting insights provided by these recent studies, the understanding of astrocyte heterogeneity in AD is still in its early days, and further studies exploring region-specificity and disease/pathology stages are still needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study and the one by Jiwaji and colleagues are highly complementary since present different methodologies. More specifically, studies used different brain regions (hippocampus vs whole cortex and spinal cord) and cell-sorting protocols that isolated distinct astrocyte populations (GFAP-positive astrocytes vs pan astrocytes) (5). Despite the exciting insights provided by these recent studies, the understanding of astrocyte heterogeneity in AD is still in its early days, and further studies exploring region-specificity and disease/pathology stages are still needed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, transcriptomics analysis in postmortem AD brains demonstrated highly variable intra-cohort astrocyte molecular signatures in individuals with the same clinical diagnosis, indicating that specific aspects of AD pathophysiology might be triggering different astrocyte phenotypes (4). In this context, Jiwaji and colleagues started uncovering the heterogeneity of astrocyte reactivity facing Aβ and tau pathologies, the neuropathological hallmarks of AD (5).…”
Section: Introductionmentioning
confidence: 99%
“…These findings corroborate that astrocyte reactivity can be triggered by inflammatory mediators released by activated microglia 4 . Moreover, recent evidence from animal models and post-mortem brain tissue demonstrated that Aβ and tau pathologies induce molecular astrocyte signatures associated with the activation of inflammatory pathways 9 . These results suggest that astrocyte reactivity might be an important component of the complex interplay between brain proteinopathies and neuroinflammation in AD.…”
Section: Discussionmentioning
confidence: 99%
“…The context-specific aspects of astrocyte reactivity 8 raise the possibility that astrocytes respond differently to AD-related brain processes. In fact, experimental evidence indicates the presence of distinct but overlapping molecular astrocyte signatures in response to Aβ and tau pathologies 9 . However, knowledge about Aβ- and tau-specific contributions to reactive astrocyte biomarkers in patients with AD is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent study of astrocyte-specific translatome changes, we investigated the separate astrocyte response to both ß-amyloidopathy and tauopathy using relevant mouse models (APP/PS1 and MAPT P301S respectively) and sequencing mRNAs associated with tagged ribosomes expressed specifically in astrocytes [ 85 ]. We found that both AD-relevant pathologies induced changes that ordinarily occur in the astrocytes of old mice and had distinct but overlapping signatures which were enriched in genes known to change in astrocytes in human AD.…”
Section: An Adaptive-protective Astrocyte Antioxidant Response Is a F...mentioning
confidence: 99%